Manajemen Preferensi Wisatawan Di Desa Wisata Kandri serta Implikasinya Bagi Pengembangan Pariwisata Berkelanjutan - Prasetyo Ardi, Rudi; Mistriani, Nina (Sekolah Tinggi Ilmu Ekonomi Surakarta, 2023)
The development of a sustainable tourism-based marketing program using a marketing mix is one of the policies in realizing sustainable tourism development. Determining a market that prioritizes the quality of experience and concern for sustainability is the cornerstone of sustainable tourism marketing. The tourism potential in Central Java, especially the tourist village, is quite potential as a tourist village area that can increase tourist visits. This research was conducted by involving 100 respondents as well as the management and local communities involved in the tourism business. The results show that the policies taken can focus on 2 segments, namely the age group less than 20 years and ages 21 to 30 years who have ecotourism preferences in realizing sustainable tourism.